Vitreoscilla Hemoglobin Improves Sophorolipid Production in Starmerella Bombicola O-13–1 Under Oxygen Limited Conditions - Li, Jun-feng; Li, Hong-fang; Yao, Shu-min; Zhao, Meng-juan; Dong, Wen-xun; Liang, Sheng-kang; Xu, Xing-yong (Frontiers in Bioengineering and Biotechnology, 2021)
Sophorolipids (SLs) are homologous microbial secondary metabolites produced by Starmerella bombicola and have been widely applied in many industrial fields. The biosynthesis of SLs is a highly aerobic process and is often limited by low dissolved oxygen (DO) levels. In this study, the Vitreoscilla hemoglobin (VHb) gene was transformed in S. bombicola O-13-1 by homologous recombination to alleviate oxygen limitation. VHb expression improved the intracellular oxygen utilization efficiency under either oxygen-rich or oxygen-limited conditions. In shake flask culture, the production of SLs was higher in the recombinant (VHb+) strain than in the wild-type (VHb-) strain, while the oxygen uptake rate of the recombinant (VHb+) strain was significantly lower than that of the wild-type (VHb-) strain. In a 5-L bioreactor, the production of SLs did not increase significantly, but the DO level in the fermentation broth of the VHb+ strain was 21.8% higher than that of VHb- strain under oxygen-rich conditions. Compared to wide-type strains (VHb-), VHb expression increased SLs production by 25.1% in the recombinants (VHb+) under oxygen-limited conditions. In addition, VHb expression increased the transcription levels of key genes involved in the electron transfer chain (NDH, SDH, COX), TCA cycle (CS, ICD, KDG1) and SL synthesis (CYP52M1 and UGTA1) in the recombinant (VHb+) strains. VHb expression in S. bombicola could enhance SLs biosynthesis and intracellular oxygen utilization efficiency by increasing ATP production and cellular respiration. Our findings highlight the potential use of VHb to increase the oxygen utilization efficiency of S. bombicola in the industrial-scale production of SLs using industrial and agricultural by-products like molasses and waste oil as fermentation feedstock.